Implantable loop recorder: experience of a center. (26th April 2021) - Marques Pires, C; Medeiros, P; Oliveira, C; Campos, I; Flores, M; Mane, F; Arantes, C; Magalhaes, S; Rocha, S; Rebelo, A; Antunes, N; Marques, J
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Symptoms like syncope and palpitations are frequent and represent a diagnostic challenge. The implantable loop recorder (LR) is an important diagnostic tool, in selected cases. AIM To describe the main implantation indications of LR and to evaluate the diagnostic findings and therapeutic interventions. METHODS: A retrospective study of patients (pts) that underwent LR implantation in our hospital from 2014 to 2019. For each pt the indication for implantation, baseline characteristics, previous study, recorded tracing and interventions were evaluated. RESULTS: A total of 52 pts were included, 56% women, with a mean age of 60 years old. The implantation indications were recurrent syncope/ presyncope in 47 pts (90%) and palpitations in 5 pts (10%). All pts had a baseline echocardiogram and electrocardiogram, with 90% in sinus rhythm. QRS complex and atrial-ventricular conduction was normal in 50% of the pts. Previous to LR implantation, 46 pts (89%) had performed Holter, 19 (37%) carotid sinus massage, 14 (27%) Tilt table test, 29 (56%) stress test, 11(21%) ambulatory blood pressure monitoring and 9 (17%) electrophysiological study. During the monitoring period, 27 pts (52%) had recurrence of the symptoms. In this subgroup, we observed that 67% had a rhythmic cause capable of justified the symptoms, with a median of 5 months since implantation until diagnosis. In addition, the LR was useful in ruling out a rhythmic cause for symptoms in 33% of the cases. In the 47 pts with syncope/presyncope: 6(13%) had sinus node dysfunction, 4 (9%) had atrioventricular conduction disturbance, 1(2%) had atrial fibrillation (AF) and 3 (6%) had ventricular dysrhythmias. In the 5 pts with palpitations: 1(20%) had AF ad 3 (60%) had paroxysmal supraventricular tachycardia. LR results led to cardiac device implantation in 13 pts (pacemaker-9, implantable cardioverter desfibrillator-4). In addition, 2 pts are waiting for electrophysiological study and eventual ablation and 3 pts initiated antiarrhythmic therapy, and those with new diagnosis of AF also initiated oral anticoagulants. CONCLUSION: In this study, the implantation of LR was useful to clarify the cause of the symptomology in 52% of the pts. In 35% of pts with symptom-rhythm correlation it ensured timely introduction of therapeutic approach with a positive impact on life quality.